2006
DOI: 10.2486/indhealth.44.17
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to Occupational Health Based on Participatory Methodology in Small Workplaces

Abstract: An intervention based on the methodology developed by the International Labour Office, the Work Improvement in Small Enterprises (WISE) was carried out to improve work condition of small-scale enterprises and the informal sector in the Philippines, Thailand and Japan. Through the evaluation of the efficacy of the approaches based on participatory methodology, it is concluded that the method is an efficient measure to improve work condition in small workplaces. It is also pointed out that the activities of supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 5 publications
1
19
0
Order By: Relevance
“…A review by Kogi points out the importance of locally tailored tools and low-cost solutions to improve work environment 9) . Itani et al revealed the necessity of support from experts when introducing and evaluating activities aimed to improve conditions at work 10) .…”
mentioning
confidence: 99%
“…A review by Kogi points out the importance of locally tailored tools and low-cost solutions to improve work environment 9) . Itani et al revealed the necessity of support from experts when introducing and evaluating activities aimed to improve conditions at work 10) .…”
mentioning
confidence: 99%
“…• Participatory action-oriented programs promoted by the International Labour Office (ILO), applying WISE (work improvement in small enterprises) methods, organized through occupational safety and health projects by trainers trained in the methods [6,16,[29][30][31][32]]. …”
Section: Participatory Programs Reviewedmentioning
confidence: 99%
“…Recent studies on the promotion of participatory programs in occupational safety, health and ergonomics clearly indicate that voluntary workplace improvements in multiple technical areas can lead to the actual reduction of work-related risks in various work situations [3,4,[10][11][12][13]. It is important to know how the application of participatory methods can help workers and managers undertake the risk-reducing work re-design in these different situations including small-scale workplaces [14][15][16][17][18][19]. It is also important to know types of support appropriate for improving working conditions particularly in small-scale workplaces despite their many constraints [6,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The ISO/TS provides practical procedures for preventing WMSDs through the reduction of local muscular workloads (LMWLs) at workplaces. The ISO/TS is based on participatory approaches taken in the practical training programs such as the WISE (Work Improvement in Small Enterprises) and the POSITIVE (Participation Oriented Safety Improvement by Trade Union InitiatiVE) which are widely applied in many countries [9][10][11][12][13][14][15] . One of the features those approaches have in common is to utilize ergonomic tools such as action-oriented checklists and group work dynamics for finding and prioritizing points to be improved and planning immediate preventive action.…”
Section: Introductionmentioning
confidence: 99%